Armored CAR T-Cells: The Next Chapter in T-Cell Cancer Immunotherapy - Hawkins ER (Dove Medical Press, 2021)
Elizabeth R Hawkins, Reena R D’Souza, Astero Klampatsa Division of Cancer Therapeutics, The Institute of Cancer Research, London, UKCorrespondence: Astero KlampatsaThoracic Oncology Immunotherapy Group, Division of Cancer Therapeutics, The Institute of Cancer Research, 15 Cotswold Road, Sutton, London, SM2 5NG, UKTel +44 208 722 4090Email astero.klampatsa@icr.ac.ukAbstract: Chimeric antigen receptor (CAR) T-cell therapy engineers T-cells to express a synthetic receptor which redirects effector function to the tumor, to improve efficacy and reduce toxicities associated with conventional treatments, such as radiotherapy and chemotherapy. This approach has proved effective in treating hematological malignancies; however, the same effects have not been observed in solid tumors. The immunosuppressive tumor microenvironment (TME) creates a significant barrier to solid tumor efficacy and reduces the anti-cancer activity of endogenous tumor-resident immune cells, enabling cancer progression. In recent years, researchers have attempted to enhance CAR T-cell function in the TME by engineering the cells to express various proteins alongside the CAR. Examples of this engineering include inducing CAR T-cells to secrete cytokines or express cytokine receptors to modulate the cytokine milieu of the TME. Alternatively, the CAR T-cell may secrete antibody-like proteins to target a range of tumor antigens. Collectively, these methods are termed armored CAR T-cell therapy, and in this review, we will discuss the range of armored CAR T-cell approaches which have been investigated to date.Keywords: armored CAR T-cells, immunotherapy, tumor microenvironment, solid tumors, immunosuppression, cell therapy